Aplicação de cálcio/magnésio e silício nas sementes de soja - Rufino, Cassyo de Araújo (2010)
The aim of this study was to evaluate the effect of coating of soybean seeds with calcium / magnesium and silicon verified through the physiological quality, yield components and plant growth. We used two micronutrients, calcium and silicon (limestone and kaolin), both at a dose of 50 g/kg-1 seed. The treatments were a combination of coating seeds and cultivars: RR Power BMX - T1 (Ca / Mg Si), T2 (Ca / Mg), T3 (Si) and T4 (No micronutrients), CD 226 RR - T1 (Ca / Mg Si), T2 (Ca / Mg), T3 (Si) and T4 (No micronutrients). For the growth analysis were analyzed the following variables: leaf area, plant height, shoot dry matter, crop growth rate (CBT), relative growth rate (RGR) and net assimilation rate (NAR). For the physiology and yield components, were performed the following tests: germination, first count germination, accelerated aging, weight of thousand seeds, seed mass per plant, plant height, stem diameter, number of pods and seeds per plant, harvest index, biological yield, total seedling length, shoot and root. For all variables analyzed were used an experimental design of randomized blocks in factorial 2x4 (two cultivars and four combinations of seed coating with Ca and Mg + Si). The coating of soybean seeds can be an alternative to seed treatment because it promotes greater leaf area and dry matter production. The plants originated from the seed coating with calcium and magnesium + silicon produced good results for the growth rate, relative growth rate and net assimilation rate of the culture. Seed coating with calcium and silicon at a dose of 50 g/100 kg presented effectiveness in the physiological performance of evaluated soybean after harvest. Cultivars BMX Power and RR 226 CD RR showed different behavior when subjected to the coating of seeds with Ca, Mg and Si.